2018
DOI: 10.1152/ajpregu.00521.2016
|View full text |Cite
|
Sign up to set email alerts
|

Mice lacking PKC-θ in skeletal muscle have reduced intramyocellular lipid accumulation and increased insulin responsiveness in skeletal muscle

Abstract: Protein kinase C-θ (PKC-θ) is a lipid-sensitive molecule associated with lipid-induced insulin resistance in skeletal muscle. Rodent models have not cohesively supported that PKC-θ impairs insulin responsiveness in skeletal muscle. The purpose of this study was to generate mice that lack PKC-θ in skeletal muscle and determine how lipid accumulation and insulin responsiveness are affected in that tissue. Mice lacking PKC-θ in skeletal muscle (SkM) and controls (SkM) were placed on a regular diet (RD) or high-fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…In addition, diet-induced obesity disrupts glucose and lipid homeostasis, resulting in long-term impairment, dysfunction, and degradation of numerous tissues, particularly the pancreas, cardiovascular, skeletal muscle, and the blood vessels [ 32 , 33 ]. Chronic HFD intake effects in the storage of intramyocellular fat in the muscle, which is one of the primary sources of whole-body glucose clearance [ 34 , 35 ]. Extra intramyocellular lipid accumulation causes 5′ adenosine monophosphate-activated protein kinase inhibition, diacylglycerol and triacylglycerol aggregation, protein kinase C activity, and impaired glucose uptake, especially in sedentary populations [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, diet-induced obesity disrupts glucose and lipid homeostasis, resulting in long-term impairment, dysfunction, and degradation of numerous tissues, particularly the pancreas, cardiovascular, skeletal muscle, and the blood vessels [ 32 , 33 ]. Chronic HFD intake effects in the storage of intramyocellular fat in the muscle, which is one of the primary sources of whole-body glucose clearance [ 34 , 35 ]. Extra intramyocellular lipid accumulation causes 5′ adenosine monophosphate-activated protein kinase inhibition, diacylglycerol and triacylglycerol aggregation, protein kinase C activity, and impaired glucose uptake, especially in sedentary populations [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lack of PKCθ protects skeletal muscle from lipidinduced insulin resistance [152]. HFD-fed mice with skeletal muscle-specific PKCθ deficiency are characterized by decreased intracellular lipid accumulation and increased insulin sensitivity in skeletal muscle, decreased fasting glucose level, and lower daily calorie intake followed by lower weight gain in comparison to control mice [153]. Moreover, it was shown that activation of PKCθ induces inhibitory phosphorylation of IRSs at several residues, e.g.…”
Section: Pkcs Suppress Insulin Sensitivity In Skeletal Muscle While Pmentioning
confidence: 99%
“…PKCθ has been mostly studied in skeletal muscle, while PKCε has been predominantly investigated in the context of the insulin-resistant liver [ 8 ]. Recent work supported the role of nPKC by showing that muscle-specific PKCθ knockout mice were protected from high-fat diet (HFD)-induced IR [ 26 ]. The molecular mechanisms by which PKC disrupts insulin signalling have also been deeply investigated.…”
Section: Causal Role Of Dags In Insulin Resistance?mentioning
confidence: 99%